Production Management Of “Panji Semirang” At Asean Panji Festival 2023 In Yogyakarta - Riqullah, Muhammad Raka; Agustina, Arinta; Pangestu, Jangkung Putra (TUMATA: Journal of Cultural and Arts Management, 2024)
ASEAN Panji Festival 2023 is an international festival involving countries in Southeast Asia. The story of Panji Semirang was the play chosen in the festival. The aim of this festival is to practice good things and provide a bridge to the community about the Panji story through several programs that are run. This research aims to determine the production management process carried out during the implementation of "Panji Semirang" at the 2023 ASEAN Panji Festival in Yogyakarta. The research method used is a descriptive qualitative research method using George R. Terry's management function theory approach, namely planning, organizing, implementing and supervising. Data collection techniques were carried out using observation, interviews and documentation. The results of the research are production management through four planning stages: the selected story, determining the city of the show, the team that will be involved, characterization in the show. At the organizing stage: job description and communication flow. at the direction stage: training for dancers and musicians. At the supervision stage: there is a role for the core team to supervise the preparation of costs and the stage manager supervises when the show starts. Based on research, the production management process for the "Panji Semirang" performance at the 2023 ASEAN PANJI Festival in Yogyakarta is in accordance with George R. Terry's management function theory, in the implementation of its production.